Soil microbial and chemical properties influenced by continuous cropping of banana - Jianbo Sun; Liangping Zou; Wenbin Li; Yuguang Wang; Qiyu Xia; Ming Peng (Scientia Agricola)
ABSTRACT: The impacts of continuous cropping of banana on soil microbiological and biochemical properties are little understood. In this study, we evaluated the variations in soil bacterial community abundance and diversity, microbial biomass carbon (MBC) and nitrogen (MBN) as well as soil enzyme activities involved in C, N and P cycles as affected by continuous cropping of banana. An initial increase in bacterial 16S rRNA copy and soil microbial biomass was observed in the second cropping and then decreased until the fourth cropping. The diversity of bacterial community showed a continuous decrease throughout the experiment. In addition, continuous cropping of banana caused shifts in bacterial community composition and structures. Soil urease and invertase exhibited the highest activities in the second cropping and then decreased gradually from the second to the fourth cropping. The phosphatase activity showed a gradual increase from the first to the third cropping. The bacterial 16S rRNA copy was positively correlated with the contents of MBN and urease activities. The results indicated that continuous cropping of banana was responsible for the disturbance of the bacterial community and that the effect on enzyme activity varies depending on the type of soil enzyme.